IMPACTS OF THE VUNG TAU - GO CONG SEA DYKE ON HYDRODYNAMIC FLOW REGIME - Lan, Nguyen Hong; Toan, Bui Duc (Vietnam Journal of Marine Science and Technology, 2017)
The low-lying terrain in downstream area of Sai Gon - Dong Nai river is mostly affected by natural disasters such as flooding, saltwater intrusion causing difficulties in process of socio-economic development. The project of building Vung Tau - Go Cong sea dyke with a length of 32 km was proposed to solve these problems, particularly creating a reservoir for storing water and preventing saltwater intrusion, expanding urban space, industrial parks, tourism, services, shelter for boats from the storm, reserving fresh water in the future. However, hydrodynamic regime in this area would be altered by the construction of Vung Tau - Go Cong sea dyke, causing sedimentation in estuaries, changing salt marsh ecosystems. The comparison between hydrodynamic regimes with two scenarios before and after construction of sea dyke will be mentioned in this paper. In this study, MIKE 21 model was used to simulate hydrodynamic regime in study area. The computed domain is described as follows: Latitude: 1080000 - 1160000 (9º44N - 10º32N); Longitude: 670000 - 770000 (106º33E - 107º33E). The grid which was used in computation was unstructured mesh because it met the requirement of accuracy and detailed computation. Exported data from MIKE 11 model was used as input data for discharge boundary of model. The observed water level data of Vung Tau station and global tide prediction data were used for model calibration and validation. Duration time of model calibration and validation for the research site was from 17/10/2000 to 20/10/2000 and from 21/10/2000 to 24/10/2000 respectively. The calibrated parameter was seabed roughness. The application of model is considered in two scenarios: Without sea dike and with sea dike. Both scenarios show semidiurnal tidal regime in Go Cong - Vung Tau area. Moreover, those confirm that current is mainly influenced by tide and flow of estuaries in coastal area. The construction of sea dike creates two distinct areas: The first area- reservoir including main dike, branch dike and Soai Rap estuary; The second area - Ganh Rai bay containing Long Tau, Thi Vai estuaries and branch dike. There is a significant change in hydrodynamic regime between two scenarios inside reservoir, for example considerable differences in phase, fluctuation amplitude of water level/current. Except for inside the reservoir, there is a small change in phase, fluctuation amplitude of water level/current outside reservoir.